What should we expect when two myositis-specific antibodies coexist in a patient - Yiming Zheng; Yawen Zhao; Hongjun Hao; Zhaoxia Wang; Feng Gao; Wei Zhang; Yun Yuan (European Journal of Medical Research, 2023)
Abstract Background The coexistence of two myositis-specific autoantibodies (MSA) is considered extremely rare. We describe three patients with both anti-signal recognition particle (SRP) antibodies and another MSA in serum. Methods We performed a retrospective clinical data collection and follow-up studies of the clinical manifestations and treatment outcome of three patients positive with anti-SRP antibodies and other MSAs. IgG antibodies against MSAs were detected using commercial line immunoblot assay. Results The tests of MSA showed positive result of anti-SRP antibodies and another one MSA including anti-TIF1-γ, anti-Jo1, or anti-EJ antibodies, respectively. The proximal muscle weakness appeared in 2 patients; interstitial lung disease presented in 2 patients. The serum CK level was elevated in 1 patient. The muscle biopsy showed necrotizing myopathy in 1 patient and deposition of membrane attack complex on scattered myofibers in the other one patient. One of the two patients with interstitial lung disease died because of respiratory failure. One patient had completely improved and the other one showed partial remission after immunosuppressive therapy. Conclusions The patients with anti-SRP antibodies co-occurred with the other MSA may have various clinical characteristics. The clinicopathological phenotypes of these patients seem to be mainly caused by one of the MSAs, namely the responsible antibody.